Optimizing Drainage Project Oversight at the Semarang City Public Works Department - Rizqika Farah Isnugraheny; Ratih Damayanti (Universitas Negeri Semarang, 2026)
Infrastructure development is an effort to improve the quality of public services, particularly in regional development. One type of infrastructure that plays a crucial role in urban area management is the drainage system. The city of Semarang is an area with complex terrain, so the implementation of drainage projects must be optimized. In this context, the responsibility for implementing drainage projects lies with the Semarang City Public Works Department. However, various challenges are frequently encountered, and strict supervision is required during implementation. The objective of this study is to assess the effectiveness of drainage project supervision in Semarang City to determine the accountability of the involved agencies. The optimization of drainage project supervision at the Semarang City Public Works Department can be viewed through the lens of Muchsan’s supervision theory, which emphasizes both external and internal controls. This includes preventive measures, such as contracts designed to prevent deviations, and corrective actions to address obstacles, ensuring the project proceeds as planned and operates optimally. This supervision involves a complex network of supervisory actors, including the Public Procurement Agency, the Internal Government Supervisory Apparatus (APIP), the State Audit Board (BPK), and the Public Works Department. The effectiveness of drainage project supervision in Semarang City heavily depends on aligning field operations with Law No. 30 of 2014 to address legal obstacles related to jurisdictional authority, which frequently pose challenges. Supervision must encompass administrative compliance to ensure legal certainty. Thus, optimal public benefit can be achieved.